Dora heita [videorecording (DVD)] - Tanikawa, Kensaku (Samurai cinema., 2007)
Koheita is a samurai with a reputation for debauchery, so his appointment as magistrate of the most corrupt township in Japan raises a few eyebrows on both sides of the law ... but is everything as it seems?